2010
DOI: 10.1007/s00221-010-2245-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of eye and hand movements to target displacements of different size

Abstract: Previous work has documented that the direction of eye and hand movements can be adaptively modified using the double-step paradigm. Here we report that both motor systems adapt not only to small direction steps (5° gaze angle) but also to large ones (28° gaze angle). However, the magnitude of adaptation did not increase with step size, and the relative magnitude of adaptation therefore decreased from 67% with small steps to 15% with large steps. This decreasing efficiency of adaptation may reflect the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
4
7
1
Order By: Relevance
“…As during the use of a computer mouse, the hand was not concealed from view. This arrangement was similar to those of other studies, which reported robust and persisting adaptation Grigorova et al 2013;Schmitz et al 2010Schmitz et al , 2012.…”
Section: Sensorimotor Adaptation: Apparatussupporting
confidence: 89%
See 4 more Smart Citations
“…As during the use of a computer mouse, the hand was not concealed from view. This arrangement was similar to those of other studies, which reported robust and persisting adaptation Grigorova et al 2013;Schmitz et al 2010Schmitz et al , 2012.…”
Section: Sensorimotor Adaptation: Apparatussupporting
confidence: 89%
“…Thus, the results are valid for such spacing, only. As shown for adaptation to rotated feedback and to double steps, generalization decreases with increasing target spacing and target steps (Bock and Schmitz 2011;Schmitz et al 2010). Future studies should investigate width and shaping of spatial generalization in relation to visual input and motor performance by varying the target spacing and the size of the sensorimotor discordance.…”
Section: Limitations and Outlookmentioning
confidence: 91%
See 3 more Smart Citations